Lock out the poor. - Frayssinet, Fabiana (New Internationalist, 2009)
The article reports on a wall that is being constructed around urban slums in Rio de Janeiro, Brazil. Human rights groups have spoken out against the concrete wall claiming that it is a form of social apartheid and is designed to separate the rich from the poor. City officials assert that the wall is being erected in order to halt urban sprawl into the country's Atlantic rainforest. The article highlights the city's need for housing.